Pesan Moderasi Beragama Akun Instagram @Mubadalah.ID Dalam Mencegah Radikalisme di Media Sosial - Mustakimah, Lina; Rosyad, Rifki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2023)
Radicalism is one of the common enemies of all religions including Islam, radicalism becomes negative because it forces ideology or will on others to follow what is the right path for them, in this digital era, prevention of radicalism is important considering that in Indonesia around 84, 94% of students who can access the internet are intolerant. Today the internet and social media are sources of reference for knowledge, including knowledge about religion. The existence of the Instagram account @mubadalah.id is very important in presenting peaceful, soothing and reassuring religious narratives which can be used as penetration for disseminating the notion of religious moderation and is expected to be able to prevent radicalism by utilizing social media. The research method used in this study is the elaboration between the analytical descriptive communication style of the Instagram account @mubadalah.id in conveying the message of religious moderation which is uploaded on his Instagram account. The results of this study found that in analyzing the message of religious moderation carried out by @mubadalah.id according to Harold Dwight Laswell we must answer several questions; who, says what, uses which channels or media, to whom and how does it affect. The conclusion from this study is that the influence of the message of religious moderation by @mubadalah.id can increase knowledge and change followers to be more tolerant and moderate.